Locus of Enterocyte Effacement: A Pathogenicity Island Involved in the Virulence of Enteropathogenic and Enterohemorragic Escherichia coli Subjected to a Complex Network of Gene Regulation - Franzin, Fernanda M. (Biomed Res Int, 2015)
The locus of enterocyte effacement (LEE) is a 35.6 kb pathogenicity island inserted in the genome of some bacteria such as enteropathogenic Escherichia coli, enterohemorrhagic E.coli, Citrobacter rodentium, and Escherichia albertii. LEE comprises the genes responsible for causing attaching and effacing lesions, a characteristic lesion that involves intimate adherence of bacteria to enterocytes, a signaling cascade leading to brush border and microvilli destruction, and loss of ions, causing severe diarrhea. It is composed of 41 open reading frames and five major operons encoding a type three system apparatus, secreted proteins, an adhesin, called intimin, and its receptor called translocated intimin receptor (Tir). LEE is subjected to various levels of regulation, including transcriptional and posttranscriptional regulators located both inside and outside of the pathogenicity island. Several molecules were described being related to feedback inhibition, transcriptional activation, and transcriptional repression. These molecules are involved in a complex network of regulation, including mechanisms such as quorum sensing and temporal control of LEE genes transcription and translation. In this mini review we have detailed the complex network that regulates transcription and expression of genes involved in this kind of lesion.